The obligation to be present at Mass on Sundays and on Holy Days of Obligation - MIERZEJEWSKI, KRZYSZTOF (Prawo Kanoniczne, 2014)
This article concerns the legal obligation to attend the celebration of Mass on Sundays and on Holy Days of Obligation. This work will define the nature and the subject of this obligation, the issues that arise and are linked to the liturgical action and the time allotted for the fulfilment of this legal duty. This article also addresses the question of who may rightly dispense from the requirement to be present at Mass on these days. The obligation to be present at Mass on Sundays and Holy Days is grounded in Divine Law. The manner of realizing the obligation is defined in positive Divine Law. The obligation to celebrate Mass is the duty of priests, and these in normal circumstances thus fulfil their duty to be present at Mass. All the faithful are required to be present at Mass on Sundays and on Holy Days of Obligation.